Why Do Large Firms' Prices Anticipate Earnings Earlier than Small Firms' Prices?* - AYERS, BENJAMIN C.; FREEMAN, ROBERT N. (Contemporary Accounting Research, 2000)
Abstract This paper presents evidence that the positive association between firm size and price leads of earnings is not solely a function of private search incentives for firm‐specific information. Specifically, we find that small‐firm prices also lag large‐firm prices with respect to industry‐wide information. Our empirical analysis extends Collins, Kothari, and Rayburn 1987 and Freeman 1987, who document that security‐price leads of earnings are positively associated with market capitalization. In particular, we examine the association between firm size and the timing of security returns for two components of annual earnings changes: the average change for a firm's industry and the firm's idiosyncratic change. We find that large firms' prices have a longer lead than small firms' prices with respect to both components. Large firms' early lead on industry‐wide earnings suggests that returns of large firms predict returns of same‐industry small firms. To test this implication, we construct a portfolio of long (short) positions in small firms when the prior month's returns of large firms in their industry are above (below) average for large firms in other industries. This zero investment portfolio earns 4.5 percent over 12 months.